2006
DOI: 10.1002/cbdv.200690017
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity Plays a Major Role in Modulating the Inhibition of Monoamine Oxidase B by 7‐Substituted Coumarins

Abstract: A series of coumarin derivatives (1-22), bearing at the 7-position ether, ketone, ester, carbamate, or amide functions of varying size and lipophilicity, were synthesized and investigated for their in vitro monoamine oxidase-A and -B (MAO-A and -B) inhibitory activities. Most of the compounds acted preferentially as MAO-B inhibitors, with IC(50) values in the micromolar to low-nanomolar range. A structure-activity-relationship (SAR) study highlighted lipophilicity as an important property modulating the MAO-B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 54 publications
5
44
0
Order By: Relevance
“…In conclusion, the present study confirmed and reinforced the validity of the interaction models proposed by our group on MAO-B inhibitors 19,20 and deepened our understanding of the structural requirements for high MAO affinity and selectivity. The easy synthetic accessibility and potentially low toxicity of coumarins make them "privileged scaffolds" for preparing new inhibitors with improved in vitro affinity.…”
Section: Conclusion and Prospectssupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, the present study confirmed and reinforced the validity of the interaction models proposed by our group on MAO-B inhibitors 19,20 and deepened our understanding of the structural requirements for high MAO affinity and selectivity. The easy synthetic accessibility and potentially low toxicity of coumarins make them "privileged scaffolds" for preparing new inhibitors with improved in vitro affinity.…”
Section: Conclusion and Prospectssupporting
confidence: 90%
“…On the basis of previous 19,20 and herein reported results, the major structural determinants of rMAO affinity and B/A selectivity were established for this biologically important and easily accessible class of natural compounds. 41 We demonstrated that rMAO affinity and selectivity can be efficiently modulated by appropriate modifications of length, size, and chemical nature of the substituents at position 7 and by introducing methyl groups in positions 3 and 4.…”
Section: Conclusion and Prospectsmentioning
confidence: 97%
See 1 more Smart Citation
“…The MAO‐B inhibitory activities of this series of tetralone derivatives can help to analyze the structure–activity relationship. The hydroxyl group introduction at R 5 position of tetralone ring system resulted in a decrease in efficacy against MAO‐B isoforms, whereas some substitutions including Br/Cl and OCH 3 on various positions of main backbone, marginally enhanced the MAO‐B inhibitory activity in some compounds in comparison with the unsubstituted homolog and this finding is also supported by previous reports . The MAO‐B activity can increase up to threefold in frontal, parietal, and temporal cortex of AD patients in comparison with healthy individuals, resulting in higher levels of oxidative free radicals and H 2 O 2 , which are known to be involved in the development of oxidative stress .…”
Section: Resultssupporting
confidence: 84%
“…This is related to the recent discovery that the increase in MAO-B activity is associated with gliosis, which can result in high levels of hydrogen peroxide and oxidative free radicals. [29] Substitution patterns at the 3-and 7-positions have been thoroughly studied. The increment of dopamine metabolism, as well as the described oxidative stress, may play a role in the etiology of ND.…”
Section: Introductionmentioning
confidence: 99%